Character Education in the Role of Independent Curriculum Through Science (IPA and IPS) - Naufal Latifah; Rifa Fauziah Kamal; Syafira Rama Dhani Novianingsih; Tin Rustini (Penerbit Hellow Pustaka, 2024)
The curriculum is the spirit of education that can never be separated. The Merdeka Curriculum is combined with the science subjects, which include science and social studies, with the aim of triggering children to manage the natural and social environment in one unit. Science learning has an important role in shaping students' character. Character education in science is expected to shape children's personalities to become good people, citizens, and good citizens. Character education is said to be important because the holders of the nation's future will be held by children who are currently in school. Character education in schools not only teaches what is right and wrong, but is also an effort to instill good habits so that students are able to behave based on the values ​​that have become their personalities.